Synthesis of Arylethylamines via C(sp3)–C(sp3) Palladium-Catalyzed Cross-Coupling - Lippa, Rhys A; Battersby, David J; Murphy, John A; Barrett, Tim N (Journal of organic chemistry, 2021)
Substituted arylethylamines represent a key structural motif in natural, pharmaceutical, and agrochemical compounds. Access to such scaffolds has been the subject of long-standing synthetic interest. Herein, we report the synthesis of such scaffolds via a palladium-catalyzed C(sp3)–C(sp3) coupling between (chloromethyl)aryls and air-/moisture-stable N,N-dialkylaminomethyltrifluoroborate salts. Rapid hit identification was achieved using microscale high-throughput experimentation and was followed by millimolar-scale reaction parameter optimization. A range of structurally and electronically varied arylethylamine products were obtained in moderate to excellent yields (27–96%, >60 examples). The reaction mechanism is proposed to proceed via formation of a trialkylbenzylammonium species prior to oxidative addition.